2017
DOI: 10.1016/j.jaci.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Parents' childhood socioeconomic circumstances are associated with their children's asthma outcomes

Abstract: Background Previous literature documents associations between low socioeconomic status (SES) and poor health outcomes, including asthma. However, this literature has largely focused on the effects of current family circumstances. Objective To test an intergenerational hypothesis, that the childhood SES that parents experience will be associated with asthma outcomes in their children, independent of effects of current family SES. Secondly, to test whether this association is in part due to difficulties in cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 73 publications
3
45
0
1
Order By: Relevance
“…Mirroring evidence of cross-generational transmission of health disparities (Pembrey et al 2014; Schreier & Chen 2010; Chen et al 2016b), we observed a consistent relationship between mothers’ childhood hardship and adverse pregnancy outcomes. Women who experienced disadvantaged childhoods were more likely to deliver preterm, SGA babies.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Mirroring evidence of cross-generational transmission of health disparities (Pembrey et al 2014; Schreier & Chen 2010; Chen et al 2016b), we observed a consistent relationship between mothers’ childhood hardship and adverse pregnancy outcomes. Women who experienced disadvantaged childhoods were more likely to deliver preterm, SGA babies.…”
Section: Discussionsupporting
confidence: 49%
“…In doing so, it draws attention to the incremental costs associated with this phenomenon, and begins to clarify some of the underlying behavioral and biological mechanisms. It also contributes to the growing literature on inter-generational effects (Pembrey et al 2014; Schreier & Chen 2010; Chen et al 2016b), and extends knowledge in this domain by highlighting pregnancy as a sensitive period during which health disparities may be transmitted across generations.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This cross-sectional analysis focuses on 99 children with asthma from either lower-SES (n = 49) or higher-SES (n = 50) families. They were drawn for a gene-expression sub-study from a larger cohort of 308 patients 19 and represent the poles of that sample's SES distribution.…”
Section: Patientsmentioning
confidence: 99%
“…It is important to consider that previous studies suggest that regardless of whether the population suffers from psychopathology, retrospective report accuracy tends to improve with salience and contextual detail (Brewin et al, 1993). Principles from cognitive psychology could aid us in this case: for example, retrospective measures with good recall performance ask for "number of rooms in your household growing up" as a proxy for developmental SES (Chen et al, 2017). Further, building techniques such as anchoring into inventories is a viable technique (e.g., discussing events in the context of seasons/school years/life-events) (Brewin et al, 1993).…”
Section: Issues Affecting Reliable and Valid Assessment Of Early Lifementioning
confidence: 99%